2020
DOI: 10.1111/cts.12902
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Therapeutic Window of Targeted Drugs in Oncology: Potency‐Guided First‐in‐Human Studies

Abstract: Many targeted therapies are administered at or near the maximum tolerated dose (MTD). With the advent of precision medicine, a larger therapeutic window is expected. Therefore, dose optimization will require a new approach to early clinical trial design. We analyzed publicly available data for 21 therapies targeting six kinases, and four poly (ADP‐ribose) polymerase inhibitors, focusing on potency and exposure to gain insight into dose selection. The free average steady‐state concentration (C ss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…Although the absolute threshold level below which the activity of palbociclib may be affected is currently unknown, it has been reported that the free average steady-state concentration (C ss ) for palbociclib was similar to the in vitro cell potency (IC 50 ), with a C ss /IC 50 ratio of 0.94. 23 Findings of the current study support the hypothesis that long-term treatment with PPIs may reduce palbociclib plasma levels below the minimum effective concentration, thus affecting its efficacy to some degree. A limitation of our study is the lack of assessment of changes in palbociclib pharmacokinetics induced by PPIs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although the absolute threshold level below which the activity of palbociclib may be affected is currently unknown, it has been reported that the free average steady-state concentration (C ss ) for palbociclib was similar to the in vitro cell potency (IC 50 ), with a C ss /IC 50 ratio of 0.94. 23 Findings of the current study support the hypothesis that long-term treatment with PPIs may reduce palbociclib plasma levels below the minimum effective concentration, thus affecting its efficacy to some degree. A limitation of our study is the lack of assessment of changes in palbociclib pharmacokinetics induced by PPIs.…”
Section: Discussionsupporting
confidence: 79%
“…Such a reduction in the ribociclib C trough is unlikely, however, to be clinically relevant due to its wide therapeutic index characterized by an average free C ss that largely exceeds the in vitro cell potency (C ss /IC 50 ratio >25). 23 Concerning abemaciclib, the drug shows similarities in pharmacokinetics compared with the other CDK4/6 inhibitors. Perhaps a feature that is worth mentioning is the saturable absorption which justifies, together with the shorter half-life and the smaller volume of distribution compared with ribociclib and palbociclib, a continuous, twice-daily administration.…”
Section: Discussionmentioning
confidence: 99%
“…When below the absolute threshold level, although it is not known at this time that the activity of palbociclib may be affected, palbociclib cell potency in vitro (IC 50 ) with free mean steady-state concentration (C ss ) is comparable with a C ss /IC 50 ratio of 0.94 [ 29 ]. The findings of the present study support the following hypothesis: prolonged treatment with PPIs may reduce palbociclib to plasma levels below the threshold of the minimum effective concentration, thus reducing its effectiveness to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…When below the absolute threshold level, although it is not known at this time that the activity of palbociclib may be affected, palbociclib cell potency in vitro (IC50) with free mean steady-state concentration (Css) is comparable with a Css/IC50 ratio of 0.94 [23]. The ndings of the present study support the following hypothesis: prolonged treatment with PPIs may reduce palbociclib to plasma levels below the threshold of the minimum effective concentration, thus reducing its effectiveness to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Saman et al reported that trough concentration mean ribociclib values (C trough ) were 597 and 711 ng/ml in patients with or without PPI at 600 mg dose, respectively [14]. On average, free C ss expressing a broad therapeutic index a reduction in ribociclib C trough , is unlikely, as it greatly exceeds in vitro cell potency (C ss /IC50 ratio >25) [23]. But in real life, almost half of the patients use Ribociclib at a dose of 400 mg.…”
Section: Discussionmentioning
confidence: 99%